2007
DOI: 10.1016/s1474-4422(07)70131-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for recurrent venous thromboembolism in the European collaborative paediatric database on cerebral venous thrombosis: a multicentre cohort study

Abstract: SummaryBackgroundThe relative importance of previous diagnosis and hereditary prothrombotic risk factors for cerebral venous thrombosis (CVT) in children in determining risk of a second cerebral or systemic venous thrombosis (VT), compared with other clinical, neuroimaging, and treatment variables, is unknown.MethodsWe followed up the survivors of 396 consecutively enrolled patients with CVT, aged newborn to 18 years (median 5·2 years) for a median of 36 months (maximum 85 months). In accordance with internati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
145
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(162 citation statements)
references
References 40 publications
5
145
0
6
Order By: Relevance
“…It is notable that children with CVLs and cancer were excluded from the study reported by Nowak-Gottl et al (2001). In a multicentre study of children with cerebral sinovenous thrombosis (SVT) the presence of the F2 (prothrombin gene) G20210A mutation was found to be associated with an increased risk of recurrence (hazard ratio 4AE3, 95% CI 1AE1-16AE2; P = 0AE034) but F5 R506Q (factor V Leiden; FVL) was not predictive of recurrence (Kenet et al, 2007). A recent systematic review showed that recurrent VTE in children is significantly associated with deficiencies of protein C, protein S and antithrombin, the F2 variant and combined genetic traits (Young et al, 2008).…”
Section: Factors Affecting Recurrence Riskmentioning
confidence: 99%
“…It is notable that children with CVLs and cancer were excluded from the study reported by Nowak-Gottl et al (2001). In a multicentre study of children with cerebral sinovenous thrombosis (SVT) the presence of the F2 (prothrombin gene) G20210A mutation was found to be associated with an increased risk of recurrence (hazard ratio 4AE3, 95% CI 1AE1-16AE2; P = 0AE034) but F5 R506Q (factor V Leiden; FVL) was not predictive of recurrence (Kenet et al, 2007). A recent systematic review showed that recurrent VTE in children is significantly associated with deficiencies of protein C, protein S and antithrombin, the F2 variant and combined genetic traits (Young et al, 2008).…”
Section: Factors Affecting Recurrence Riskmentioning
confidence: 99%
“…SVT has been often a multi factorial disease, i.e the identification of a risk factor or even of a cause should not deter a search for other causes (5,6). Several studies, have described some of the well-established risk factors for SVT that include inherited thrombophilia such as factor V Leiden mutation, protein C and S deficiency, acquired prothrombotic state (pregnancy, purperium and postsurgical period), hepatic dysfunction ,autoimmune disease (Behçet syndrome, systemic lupus erythematosus), malignancy (lung cancer, blood dyscrasia, systemic carcinoma), systemic infectious disease, local infection of the skull (e. (7)(8)(9)(10)(11)(12)(13)(14). Nagesh Kumar reported a case of a 35 years old male who presented to the emergency center with drowsiness and focal seizures leading to grand seizures and loss of consciousness.…”
Section: Discussionmentioning
confidence: 99%
“…Heparin arrests the thrombotic process and may prevent the development of infarcts. Despite the risk of hemorrhagic complications, anticoagulation is associated with a potentially important reduction in the risks of death and neurologic morbidity in adults, and of recurrence in children [19,20]. The other treatment option in patients with DSVT is thrombolysis.…”
Section: Discussionmentioning
confidence: 99%